Improvement in the water retention characteristics of sandy loam soil using a newly synthesized poly(acrylamide-co-acrylic acid)/AlZnFe2O4 superabsorbent hydrogel nanocomposite material - Shahid, Shaukat Ali; Qidwai, Ansar Ahmad; Anwar, Farooq; Ullah, Inam; Rashid, Umer (MDPI, 2012)
The use of some novel and efficient crop nutrient-based superabsorbent hydrogel nanocomposites (SHNCs), is currently becoming increasingly important to improve the crop yield and productivity, due to their water retention properties. In the present study a poly(Acrylamide-co-acrylic acid)/AlZnFe2O4 superabsorbent hydrogel nanocomposite was synthesized and its physical properties characterized using Energy Dispersive X-ray (EDX), FE-SEM and FTIR spectroscopic techniques. The effects of different levels of SHNC were studied to evaluate the moisture retention properties of sandy loam soil (sand 59%, silt 21%, clay 19%, pH 7.4, EC 1.92 dS/m). The soil amendment with 0.1, 0.2, 0.3 and 0.4 w/w% of SHNC enhanced the moisture retention significantly at field capacity compared to the untreated soil. Besides, in a separate experiment, seed germination and seedling growth of wheat was found to be notably improved with the application of SHNC. A delay in wilting of seedlings by 5–8 days was observed for SHNC-amended soil, thereby improving wheat plant growth and establishment.